2010
DOI: 10.1097/lgt.0b013e3181e9635b
|View full text |Cite
|
Sign up to set email alerts
|

Random Biopsy After Colposcopy-Directed Biopsy Improves the Diagnosis of Cervical Intraepithelial Neoplasia Grade 2 or Worse

Abstract: The detection of CIN 2+, particularly high-grade cytological abnormalities and large lesion size, can be increased by additional random biopsies after satisfactory colposcopy. Loop electrosurgical excision procedure conization can detect lesions not detected by punch biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…Studies have shown that conventional biopsy protocols miss up to 30% of prostate cancers, which has led to recommendations of extended biopsy procedures [22]. In other studies on cervical biopsies, multiple non-directed biopsies were collected and it was estimated that 10-30% of CIN2 + were found by these nondirected biopsies [5,7,8,23]. In our study, the total additional benefit of non-directed biopsies for detecting CIN2 + was 25/182 (13.7%; Table 3).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Studies have shown that conventional biopsy protocols miss up to 30% of prostate cancers, which has led to recommendations of extended biopsy procedures [22]. In other studies on cervical biopsies, multiple non-directed biopsies were collected and it was estimated that 10-30% of CIN2 + were found by these nondirected biopsies [5,7,8,23]. In our study, the total additional benefit of non-directed biopsies for detecting CIN2 + was 25/182 (13.7%; Table 3).…”
Section: Discussionmentioning
confidence: 72%
“…In a study investigating women with atypical cells of undetermined significance (ASC-US) cytology and CIN3 or invasive cervical cancer (ICC), it was found that gains in detecting cervical precancer can be obtained by increasing the number of lesion-directed biopsies from one to two [6]. Moreover, in studies that include biopsies of regions without colposcopic abnormality in addition to lesion-directed biopsies, 12 to 37% of the overall CIN2+ lesions were detected in this biopsy only [5,7,8].…”
mentioning
confidence: 95%
“…These studies report an improvement in detection of CIN2+ with increased by biopsy collection can be increased by as much as 37%. 18,[37][38][39] The involvement of colposcopists in the systematic collection of biopsies will be an important step to ensure the detection of CIN2 + cases that require prompt treatment. The FRIDA Study will also document the benefit of adopting a systematic collection of cervical biopsies as routine colposcopy practice.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Given the high prevalence of positive ECCs in our population of women who ultimately underwent therapy, the marginal utility of performing an ECC in cases where an excisional specimen validated the highest grade of dysplasia shows it contributed significantly to the discovery of CIN 2+ in that cohort, even among satisfactory colposcopies. This high correlation of ECC practice toward finding CIN 2+ resulting from thorough colposcopic biopsy practice and ultimate excision should not be confused with its use prospectively and the likelihood of an ECC contributing exclusively to the diagnosis of CIN 2+ in all patients referred to colposcopy (regardless of treatment status), which is lower.…”
Section: Discussionmentioning
confidence: 98%